2022
DOI: 10.1038/s41385-021-00467-7
|View full text |Cite
|
Sign up to set email alerts
|

Human mucosal tissue-resident memory T cells in health and disease

Abstract: Memory T cells are fundamental to maintain immune surveillance of the human body. During the past decade, it has become apparent that non-recirculating resident memory T cells (TRMs) form a first line memory response in tissues to tackle re-infections. The fact that TRMs are essential for local immunity highlights the therapeutic potential of targeting this population against tumors and infections. However, similar to other immune subsets, TRMs are heterogenous and may form distinct effector populations with u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 36 publications
(23 citation statements)
references
References 149 publications
(191 reference statements)
0
23
0
Order By: Relevance
“…T cells constitute an important part of the intestinal immune machinery. Recent data indicate that in particular T resident memory cells act as immune sentinels against invading pathogens 18 . We, therefore, evaluated the intestinal T‐cell compartment in duodenal biopsies from healthy controls and in actively drinking AUD patients.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…T cells constitute an important part of the intestinal immune machinery. Recent data indicate that in particular T resident memory cells act as immune sentinels against invading pathogens 18 . We, therefore, evaluated the intestinal T‐cell compartment in duodenal biopsies from healthy controls and in actively drinking AUD patients.…”
Section: Resultsmentioning
confidence: 99%
“…Recent data indicate that in particular T resident memory cells act as immune sentinels against invading pathogens. 18 We, therefore, evaluated the intestinal T-cell compartment in duodenal biopsies from healthy controls and in actively drinking AUD patients. Immunohistochemistry revealed that the number of CD8+ T lymphocytes was lower in actively drinking AUD patients compared with healthy controls (Figure 1A,B).…”
Section: Reduced Duodenal Cd8+ T Resident Memory Lymphocytes Characte...mentioning
confidence: 99%
“…Unlike other memory T cells such as central memory and effector memory T cells, T RM cells colonize local tissues infected by pathogens and remain there for a long time after the pathogen has been eliminated without participating in blood circulation (129). They have been demonstrated at sites that include the intestines, skin, urogenital tract, and lung mucosa (130)(131)(132)(133). When the pathogen invades again, T RM cells immediately sense and initiate immune responses so that the pathogen can be controlled or be eliminated at the early stage of infection.…”
Section: T Rm -Mediated Anti-tb Immune Protectionmentioning
confidence: 99%
“…The mucosal immune system is the first defence line because it is the initial site of interaction most of the disease causing pathogens (Chassaing et al, 2014;Jung et al, 2010;Macpherson & Smith, 2006). Pathogens can infiltrate mucosal membranes in the aerodigestive, respiratory and urogenital tracts because they have frequent contact with the outside environments (Lange et al, 2021).…”
Section: Development Of Oral Vaccinementioning
confidence: 99%